Behavior and Expectations of Receiving Services Among Patients with Common Illnesses in Drug Stores under the Universal Health Coverage System, Sukhothai Province - Thongruang, Sanit; Singweratham, Noppcha; Boonchieng, Waraporn; Tiemyen, Wanwisa (Journal of Public Health and Innovation, 2026)
This mixed-methods research aimed to study the service utilization behaviors and expectations on Common illness care in pharmacies under the Universal Health Coverage (UC) among patients in Sukhothai province. The study consisted of two components. The quantitative component included 246 participants selected through multistage sampling. Data were collected using a structured questionnaire and analyzed using descriptive statistics. The qualitative component involved 18 key informants. Data were collected through in-depth interviews using a semi-structured interview guide and analyzed by content analysis. The findings revealed that, regarding service utilization behaviors, most patients chose to seek services at community pharmacies because of the convenience and rapid access to medicines provided by nearby pharmacies (91.1%). Other important factors included the absence of out-of-pocket expenses and the avoidance of hospital visits (42.7%), the availability of trustworthy pharmacists providing professional advice (34.6%), and the ability to immediately utilize UCS entitlements through simple and time-saving procedures. Patients reported high expectations across all dimensions of pharmacy services. Regarding facilities and equipment, adequate and complete medicine supplies were expected to be maintained by pharmacies (Mean ± SD = 4.6 ± 0.4). In terms of service activities, pharmacists were expected to select appropriate medications and assess patients’ symptoms before dispensing medicines (Mean ± SD = 4.7 ± 0.4). For service processes, confidentiality and protection of patients’ treatment information were highly expected (Mean ± SD = 4.7 ± 0.3). Concerning personnel, pharmacists were expected to possess strong professional knowledge and competencies (Mean ± SD = 4.8 ± 0.3). The “30-Baht Pharmacy Project for 32 Common Illnesses” has enhanced public access to healthcare services by positioning community pharmacists as alternative providers for patients with minor ailments. Consequently, community pharmacies now constitute an important component of the primary healthcare system under Thailand’s Universal Coverage Scheme.